The Effect of an Educational Intervention on Health Literacy and the Adoption of Nutritional Preventive Behaviors Related to Osteoporosis Among Iranian Health Volunteers - Leila Dehghankar; Rahman Panahi; Elham Hasannia; Fatemeh Hemmati; Fatemeh Samiei Siboni (Korean Society for Preventive Medicine, 2021)
Objectives Given the increase in osteoporosis among health volunteers and the effect of health literacy on the adoption of nutritional preventive behaviors, this study aimed to determine the effects of an educational intervention on health literacy and the adoption of nutritional preventive behaviors related to osteoporosis among health volunteers. Methods This was a quasi-experimental, interventional study of health volunteers conducted in 2020. In this study, 140 subjects (70 in both intervention and control groups) were selected using the random multi-stage sampling method. An educational intervention was conducted using the Telegram application, and educational messages were sent to the health volunteers in the intervention group across 6 sessions. Data were collected via a demographic questionnaire, the Health Literacy for Iranian Adults survey, and a nutritional performance questionnaire, which were completed before and 3 months after the intervention. The data were collected and analyzed using SPSS version 23. Results Before the intervention, there were no significant differences in the mean scores for health literacy variables and the adoption of nutritional preventive behaviors between the intervention and control groups (p>0.05). After the intervention, there was a significant change in the mean scores for health literacy and the adoption of preventive behaviors in the intervention group (p<0.05) as opposed to the control group. Conclusions Interventions aimed at increasing health literacy are effective for promoting the adoption of preventive and healthy nutritional behaviors related to osteoporosis.